Oral delivery of Bifidobacterium longum expressing α-melanocyte-stimulating hormone to combat ulcerative colitis. Issue 2 (1st February 2016) - Wei, Pijin; Yang, Yan; Ding, Qing; Li, Xiuying; Sun, Hanxiao; Liu, Zhaobing; Huang, Junli; Gong, Yahui
Abstract : α-Melanocyte-stimulating hormone (α-MSH) is a tridecapeptide derived from pro-opiomelanocortin that exhibits potent anti-inflammatory properties by regulating the production of inflammatory mediators. This peptide has been well established in several inflammatory models, including inflammatory bowel disease (IBD). However, its extremely short duration in vivo limits its clinical application. To address this limitation, Bifidobacterium was used here as a carrier to deliver α-MSH. We utilized α-MSH-engineered Bifidobacterium against IBD, which is closely linked to immune and intestinal microbiota dysfunction. First, we constructed a Bifidobacterium longum secreting α-MSH ( B. longum -α-MSH). We then tested the recombinant α-MSH expression and determined its bioactivity in HT-29 cells. To assess its effectiveness, B. longum -α-MSH was used against an ulcerative colitis (UC) model in rats induced by dextran sulfate sodium. The data showed that α-MSH expression in B. longum -α-MSH was effective, and its biological activity was similar to the synthesized one. This UC model experiment indicated that B. longum -α-MSH successfully colonized the intestinal gut, expressed bioactive α-MSH and had a significant anti-inflammatory effect. The results demonstrate the feasibility of preventing IBD by using B. longum -α-MSH.